2022
DOI: 10.1177/16878132221133712
|View full text |Cite
|
Sign up to set email alerts
|

Surveying the effects of concave obstacles with different edge walls on hollow glycerin droplet impacting using the volume of fluid approach

Abstract: The numerical analysis of the impact of a hollow droplet on a solid concave obstacle at various heights of the edge wall and impact velocity is presented in this study. The Volume Of Fluid (VOF) approach was used to simulate hollow droplet impact using OpenFoam software. The Newtonian, incompressible, and laminar properties of the glycerin hollow droplet are assumed. Hollow droplet collision hydrodynamic behavior and jet characteristics were explored. The height of the counter jet rose as the impact velocity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
(20 reference statements)
0
0
0
Order By: Relevance
“…In recent years, many scholars have conducted indepth studies on the kinetic properties of single droplet. [6][7][8][9] Yin et al 10 used numerical methods to study the spreading and slipping characteristics of a single droplet colliding an inclined hydrophobic surface. It was found that the maximum spreading diameter of the droplet becomes larger as the inclination angle of the wall increases, and the oscillation of the droplet becomes stronger and more unstable.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many scholars have conducted indepth studies on the kinetic properties of single droplet. [6][7][8][9] Yin et al 10 used numerical methods to study the spreading and slipping characteristics of a single droplet colliding an inclined hydrophobic surface. It was found that the maximum spreading diameter of the droplet becomes larger as the inclination angle of the wall increases, and the oscillation of the droplet becomes stronger and more unstable.…”
Section: Introductionmentioning
confidence: 99%